PENGGUNAAN TEKNIK ANALISIS DALAM PENGEMBANGAN SISTEM INFORMASI MENGGUNAKAN SOFT SYSTEM METHODOLOGY (SSM) - Sumadyo, Malikus (LPPM Universitas Islam 45 Bekasi, 2016)
ABSTRACT Soft Systems Methodology (SSM) is a systematic method of information system development using a structured approach to understanding an issue, building a conceptual mode, getting the feasibility and the desired changes and to be implemented. The system being developed using Soft Systems Methodology aimed at addressing organizational, which is used to respond to the symptoms caused by an underlying problem that has not been previously known. Organizations can be regarded as an open system so that the relationship between the organization and the surrounding environment become the systemic relationships that are considered important. And SSM is a methodology that makes the problem situation in an organization become part of a perspective view of a problem. The use of CATWOE technique is one of the techniques in SSM stages mainly in the stage of disclosure in a structured problem situations. However, not all paper explicitly using this technique. What is the comparison between the use of the technique CATWOE and other techniques in the development of the information system using the SSM. This paper explains the techniques in implementing SSM in various areas of the organization Keyword: Soft System Methodology (SSM), CATWOE, information system development ABSTRAK Soft System Methodology (SSM) adalah metode sistematis pengembangan sistem informasi dengan menggunakan pendekatan terstruktur untuk memahami suatu masalah, membangun mode konseptual, mendapatkan kelayakan dan perubahan yang diinginkan serta mengimplementasikannya. Sistem Informasi yang dikembangkan menggunakan Soft System Methodology ditujukan untuk menangani masalah organisasional, yang digunakan untuk merespon gejala yang disebabkan oleh masalah yang mendasar yang belum diketahui sebelumnya.Organisasi dapat dikatakan sebagai sebuah sistem terbuka sedemikian rupa sehingga hubungan antara organisasi dengan lingkungan sekitarnya menjadi hubungan sistemik yang dianggap penting. Dan SSM adalah metodologi yang menjadikan situasi masalah dalam suatu organisasi sebagai bagian dari cara pandang melihat sebuah masalah.Penggunaan teknik CATWOE adalah salah satu dari teknik dalam tahapan SSM terutama dalam tahap pengungkapan situasi masalah secara terstruktur. Namun tidak semua paper secara eksplisit menggunakan teknik ini. Bagimana perbandingan penggunaan diantara teknik CATWOE maupun terhadap teknik-teknik lain dalam pengembangan sistem informasi menggunakan SSM. Paper ini menjelaskan mengenai beberapa teknik dalam mengimplementasikan SSM dalamberbagai bidang organisasi. Keyword : Soft System Methodology (SSM), CATWOE,pengembangan sistem informasi